The Appropriation of Religiousity in the 2024 Indonesian Presidential - Lindgren, Tomas; Prasojo, Zaenuddin Hudi; Bugov, Dobrin Tsvetanov; Riduan, Imam Malik; Anam, Khoirul (IAS Journal of Localities, 2024)
Religious appropriation is a phenomenon that is continually reproduced in every electoral contestation. However, this context has not been discussed comprehensively in previous studies. In addition to responding to the shortcomings of previous studies, this study also focuses on explaining the characteristics, factors, and latent dangers of religious appropriation that occured in the 2024 Indonesian presidential election. This study reveals three important findings regarding the religious appropriation in the 2024 Indonesian presidential election. First, religious appropriation frequently manifests in the context of doctrine, language, and religious behaviors expressed outside the values and norms of religion. Second, cultural, spiritual, and structural factors have dominantly influenced the occurance of religious appropriation in the 2024 Indonesian presidential election. Third, the latent dangers of religious appropriation in the 2024 Indonesian presidential election often leads to intolerance, polarization, and persecution against religious communities even after the 2024 Indonesian presidential election. This study also recommends the importance of further studies that explain the attitudes of both formal and informal authorities in responding to religious appropriation in political contestation by conducting intensive interviews.